Hygroscopic growth and activation changed submicron aerosol composition and properties in the North China Plain - Xu, Weiqi; Kuang, Ye; Xu, Wanyun; Zhang, Zhiqiang; Luo, Biao; Zhang, Xiaoyi; Tao, Jiangchuang; Qiao, Hongqin; Liu, Li; Sun, Yele (Atmospheric chemistry and physics, 2024)
Aerosol hygroscopic growth and activation under high-relative-humidity (RH) conditions significantly influence the physicochemical properties of submicron aerosols (PM1). However, this process remains poorly characterized due to limited measurements. To address this gap, we deployed an advanced aerosol–fog sampling system that automatically switched between PM1, PM2.5 and total suspended particulate (TSP) inlets at a rural site in the North China Plain in the cold season. The results revealed that aerosol swelling due to water vapor uptake influenced aerosol sampling under high-RH conditions by shifting the cut-off size of impactors. At subsaturated high RH (> 90 %), over 25 % of aerosol mass with dry diameters below 1 µm resided in supermicron ranges, while in supersaturated foggy conditions, more than 70 % of submicron aerosol migrated to supermicron ranges. Hygroscopic growth and activation particularly affected highly hydrophilic inorganic salts, shifting a significant number of submicron sulfate and nitrate particles to supermicron ranges, with 27 %–33 % at 95 % ≤ RH ≤ 99 % and more than 78 % under supersaturated foggy conditions. Moreover, more than 10 % of submicron biomass burning organic aerosols grew beyond 2.5 µm during fog events, while fossil-fuel-related organic aerosol (FFOA) remained dominantly in submicron ranges, suggesting inefficient aqueous conversion of FFOA. The two secondary organic aerosol (SOA) factors (OOA1 and OOA2) behaved differently under supersaturated conditions, with OOA2 exhibiting a higher activated fraction despite a lower oxygen / carbon ratio. A substantial increase in organic nitrate and organosulfur mass concentrations in activated droplets during fog events suggested aqueous conversions and formations of brown carbon with potential radiative impacts. Overall, our study highlights remarkably different cloud and fog processing behaviors between primary and secondary aerosols, which would benefit a better understanding of aerosol–cloud interactions under distinct atmospheric conditions.